2004
DOI: 10.1128/aac.48.6.2000-2006.2004
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility of Candida Species to Photodynamic Effects of Photofrin

Abstract: The in vitro susceptibility of pathogenic Candida species to the photodynamic effects of the clinically approved photosensitizing agent Photofrin was examined. Internalization of Photofrin by Candida was confirmed by confocal fluorescence microscopy, and the degree of uptake was dependent on incubation concentration. Uptake of Photofrin by Candida and subsequent sensitivity to irradiation was influenced by culture conditions. Photofrin uptake was poor in C. albicans blastoconidia grown in nutrient broth. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
126
1
8

Year Published

2006
2006
2011
2011

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 149 publications
(148 citation statements)
references
References 25 publications
11
126
1
8
Order By: Relevance
“…[17][18][19][20][21][22][23][24] The results of the present investigation demonstrated significant reduction of CFU/mL of C. albicans from tongues of mice after 400, 500, and 1000 mg/L of Photogem associated with LED light (305 J/cm 2 ) (455 and 630 nm). There is only one report describing a dose-dependent photoeradication of C. albicans in an immunodeficient murine model.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations
“…[17][18][19][20][21][22][23][24] The results of the present investigation demonstrated significant reduction of CFU/mL of C. albicans from tongues of mice after 400, 500, and 1000 mg/L of Photogem associated with LED light (305 J/cm 2 ) (455 and 630 nm). There is only one report describing a dose-dependent photoeradication of C. albicans in an immunodeficient murine model.…”
Section: Discussionsupporting
confidence: 55%
“…A dose-dependent inhibition of metabolic activity was observed after treatment of C. albicans strains with Photofrin (0.01 to 10 mg/L) and illumination with a light fluence of 9 J/cm 2 from an Hg arc lamp. 20 Chabrier-RosellĂł et al 23 also observed a dose-dependent reduction of metabolic activity of C. albicans biofilms mediated by 10 mg/L of Photofrin and with broadbrand illumination by visible light at fluences ranging from 0.9 to 18 J/cm 2 . However, it has been shown that photosensitization of Candida and subsequent susceptibility to PDT can be reduced dramatically by culture conditions, such as the type of culture medium and the presence of albumin.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…For this reason, there has been an increased interest in developing PDT for local infections treatment. Different types of PS have been proposed in laboratory investigations, including porphyrins [14,15], phenothiazine dyes [16,17], chlorins [18,19], and phthalocyanines [20]. However, complete killing of the microorganisms is not frequently achieved and some of the available PS showed limited effectiveness against Candida biofilms and animal models of candidiasis [15,21].…”
Section: Introductionmentioning
confidence: 99%